2016
DOI: 10.17815/cd.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

The Inflection Point of the Speed-Density Relation and the Social Force Model

Abstract: It has been argued that the speed-density diagram of pedestrian movement has an inflection point [1] (p. 3, "Domain I: ... At low densities there is a small and increasing decline of the velocity ... Domain III: ... For growing density the velocity remains nearly constant."). This inflection point was found empirically in investigations of closed-loop single-file pedestrian movement.The reduced complexity of single-file movement does not only allow a higher precision for the evaluation of empirical data, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The reduction to nearest neighbor interactions made the analytical investigation much easier, but obviously this step implies that results cannot be exact. It may be interesting in this regard that it was found that the approach of considering all other pedestrians as having an impact on a certain pedestrian does not lead to the most realistic speed–density relation, but that cutting forces at a certain number or at least suppressing them with more remote neighborhood degree is beneficial ( 26 , 27 ). Thus the approximation of nearest neighbor interaction can also be interpreted as an improvement of the model.…”
Section: Derivation Of Resultsmentioning
confidence: 99%
“…The reduction to nearest neighbor interactions made the analytical investigation much easier, but obviously this step implies that results cannot be exact. It may be interesting in this regard that it was found that the approach of considering all other pedestrians as having an impact on a certain pedestrian does not lead to the most realistic speed–density relation, but that cutting forces at a certain number or at least suppressing them with more remote neighborhood degree is beneficial ( 26 , 27 ). Thus the approximation of nearest neighbor interaction can also be interpreted as an improvement of the model.…”
Section: Derivation Of Resultsmentioning
confidence: 99%
“…Second, it was possible before to solve the SFM analytically for single file movement [13,14] which allowed to derive equations with which model parameter values can be computed from observables [15]. The latter is a decidedly valuable result since it allows direct calibration of the model (with all limitations following from approximations made as part of the analysis).…”
Section: Motivationmentioning
confidence: 99%